A randomized, placebo-controlled pilot study of upamostat, a host-directed serine protease inhibitor, for outpatient treatment of COVID-19. (March 2023) - Plasse, Terry F; Delgado, Belkis; Potts, Jeffrey; Abramson, Danielle; Fehrmann, Clara; Fathi, Reza; McComsey, Grace A
Highlights: Upamostat at specified doses used was well tolerated, without significant side effects. Entry criteria enhanced the hospitalization rate in the placebo group. Dose-dependent increased international normalized ratio and partial thromboplastin time and decreased d-dimer levels were observed. Upamostat speeded resolution and decreased the incidence of new severe symptoms. No upamostat patients were hospitalized because of COVID-19. Abstract: Objectives: We performed a pilot study of upamostat, a serine protease inhibitor, in outpatients with symptomatic COVID-19 before a pivotal trial. Methods: SARS-CoV-2 patients with ≥2 moderate-severe symptoms onset within 5 days were randomized to oral upamostat 200 or 400 mg or placebo daily for 14 days. Patients completed COVID-19 symptom questionnaires daily for 28 days, then thrice weekly for 4 weeks, and underwent physical and laboratory examinations periodically. Results: A total of 61 patients enrolled of which 20 received a placebo or upamostat 200 mg daily; 21 received upamostat 400 mg daily. Treatment was well tolerated; only one patient (upamostat 400) reported a drug-related adverse event, mild skin rash; no patient discontinued owing to a drug-related adverse event. The median time to a sustained recovery from severe symptoms was 8, 4, and 3 days for the three treatment groups, respectively. New severe symptoms developed in 20% of the placebo group vs 2.4% in the combined upamostat groups, ( P  = 0.036). Three placebo patients (15%) versus no upamostat patients were hospitalized for worsening COVID ( P = 0.03). The mean d-dimer level remained constant in placebo patients but decreased by 38% and 48% in upamostat 200 and 400 patients, respectively. Conclusion: Upamostat was well tolerated, shortened recovery time, and decreased new severe symptoms and hospitalization.